2020
DOI: 10.3389/fpsyg.2020.587270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tool Novelty and Action Demands on Gaze Searching During Tool Observation

Abstract: Technical reasoning refers to making inferences about how to use tools. The degree of technical reasoning is indicated by the bias of the gaze (fixation) on the functional part of the tool when in use. Few studies have examined whether technical reasoning differs between familiar and unfamiliar novel tools. In addition, what effect the intention to use the tool has on technical reasoning has not been determined. This study examined gaze shifts in relation to familiar or unfamiliar tools, under three conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…According to the ndings we report here, the visual exploration of unfamiliar graspable objects seems to be characterised by an explorative gaze behaviour rstly aimed at identifying the object's function and identity by looking at its functional area (Natraj et al, 2015;Van Der Linden et al, 2015;Tamaki et al, 2020). After such a preliminary semantic-driven visual exploration of the stimulus, we found that participants oriented their visual-spatial attention toward the object's manipulation areas, as if they were to prepare themselves for action (Riddoch et al, 2003;Handy et al, 2003).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…According to the ndings we report here, the visual exploration of unfamiliar graspable objects seems to be characterised by an explorative gaze behaviour rstly aimed at identifying the object's function and identity by looking at its functional area (Natraj et al, 2015;Van Der Linden et al, 2015;Tamaki et al, 2020). After such a preliminary semantic-driven visual exploration of the stimulus, we found that participants oriented their visual-spatial attention toward the object's manipulation areas, as if they were to prepare themselves for action (Riddoch et al, 2003;Handy et al, 2003).…”
Section: Discussionmentioning
confidence: 54%
“…The visual exploration of unfamiliar but graspable objects appears to re ect the interactions between affordance-based (e.g., Humphreys et al, 2013;Masson et al, 2011) and higher-level cognitive processing (e.g., Wurm & Caramazza, 2019;Bar et al, 2006). Additionally, as we mentioned above, the exploration of objects' functional areas might also be associated with technicalknowledge processing through which observers may reason about how objects can be used with other objects mechanically (e.g., looking at the head of a hammer, thus focusing on the action-performing area that will hit a nail; Tamaki et al, 2020;Goldenberg & Spatt, 2009). In this sense, our results align with multiple studies that have shown how participants may concentrate on the action's goal component more than on its manipulation component (e.g., Massen & Prinz, 2007;Osiurak & Badets, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations